Remote sensing technologies in supporting sustainable development goals (SDGS) indicators in Malays - Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Mazlan, Hashim (2017)
SDG 11 aims to make “cities and human settlements inclusive, safe, resilient and sustainable.” Hence, achieving this Goal depends in part on the level of engagement of local stakeholders, regional governments, community-based organizations, academia and the business sector, as well as on adequate synergies between national and local policies. Malaysia was deal the practice of urban and regional planning to form the shape of places, which has lead the new idea to outfit the issues of rapid urbanization. Parallel to this, the development of technologies and data tools such as Geographical Information System (GIS) and Remote Sensing (RS) were greatly increased and tend to become important tools in support of urban planning decision making. However, compare to GIS, the application of remote sensing data in Malaysia has not fully explored lack of administrator awareness and RS expertise in urban and regional planning. Therefore, this study reviewed a development and effort that have been done by all stakeholders for remote sensing development in Malaysia in the context of urban development. The linkages between the SDGs and Remote sensing technology may seem apparent, but there are open questions regarding: implementation and efficiency at the local level; the importance of this application in realizing the sustainable mission in this country; and the means by which local governments can find a potential at the nexus of the space technologies and the SDGs for future sustainable social and economic development.